The stability of thin-walled composite cylinder using Southwell plot / Darwin Sebayang (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2007)
The thin- walled composite cylinder is widely used in aerospace structures (such as rocket). This paper shows the calculation of the stability or the critical load using the Southwell plot in which the stability equation uses a transfer matrix method. The transfer matrix was formed by deriving the partial differential equation based on the equation of a cylinder which will be integrated in the circumferential direction using the Fourier series and integrated in the axial direction using the Lie-Magnus or Piccard iteration. The method was applied to different types of layer of a composite material under various load. The result of this method was compared with analytical method with satisfactory results.